"My Progress Comes From the Kids": Portraits of Four Teachers in an Urban Turnaround School. (December 2021) - Peck, Craig M.; Reitzug, Ulrich C.
This article uses elements of narrative and portraiture to acknowledge the voices of four teachers who participated in a 3-year effort to turn around an urban elementary school. Turnaround is a sanctioned reform effort intended to produce rapid, dramatic improvement in student academic achievement in a low-performing school. We present the teacher portraits as descriptive testimony to the individuals' work under turnaround conditions. We conclude by offering some educational improvement solutions tailored to address specific issues reflected in our participants' portraits.